Hypoxia exacerbates heat stress effects on the porcine intestinal epithelium in vitro - Pearce, S. C.; Gabler, N. K. (Frontiers in Animal Science, 2023)
Heat stress (HS) negatively impacts human health, as well as animal agriculture. The mechanisms underlying HS-induced intestinal dysfunction in vivo are still not fully elucidated. However, HS has been shown to cause intestinal ischemia/hypoxia, which contributes to reduced barrier integrity. The objective of this study was to examine hypoxia alone, HS alone, and a combination using IPEC-J2 cells. We hypothesized that hypoxia is a critical factor and important step in the pathway to HS-induced barrier dysfunction. Porcine IPEC-J2 cells were grown in Transwell™ plates and then treated either under thermal neutral (TN; 38°C) or heat stress (HS; 42°C) and either normoxia (NX; 21% O2) or hypoxia (HX; 1% O2) conditions for 24 h. Transepithelial electrical resistance, paracellular permeability marker, FITC-dextran, media interleukin 8, cell HSP70 and 90, CLDN4, ZO-1, and EEA1 were all analyzed. Results showed that HS did not increase intestinal permeability in this model and elicited a reduction in IL-8 while still exhibiting a robust HSP response. In this model, hypoxia was required to induce intestinal barrier dysfunction and TJ redistribution. The combination of HS and hypoxia caused even more severe tight junction disruption. This was accompanied by the absence of an IL-8 response under HS.